GE_GERICHTE P/2306/2013 vom 20. Mai 2014 - GE Cour de justice (2014)
MENDICITÉ; CEDH; LIBERTÉ D'EXPRESSION; DISCRIMINATION RACIALE | CEDH.10.1; CEDH.10.2; CEDH.8; LPG.11A; CPP.219.5; CPP.217.3; Cst.8.2; CP.52